(untitled) (FUDMA JOURNAL OF SCIENCES, 2023)
The Paint and coatings industry produces a huge variety of products that protect, preserve, and also beautify the objects to which they are applied, however, the components are expensive, therefore there is the need to look for alternative constituents which are cheaper and more durable. Emulsion Paints were formulated using colourants produced from diisocyanates and 1,4 diamino anthraquinone and polyvinyl alcohol as binder. The constituents of the paint was stirred mechanically in a ceramic mortar and pestle for 1 hour, and it was applied on the substrate (ceiling board). The coated samples were subjected to physical characterization, viscosity, surface drying time, weathering and lightfastness and compared with a commercial paint (Emulsion paint). The results indicates a very good light fastness property of 6-7, for paints produced from hexamethylene diisocyanate and where resistant to weathering, while paints produced from 1,4 phenylene diisocyanate showed a poor light fastness of 1-2, however it also indicated resistant to weathering. Hexamethylene diisocyanate, is less expensive and is more durable and economical in emulsion paint production compared to 1,4 phenylene diisocyanate which fades easily and is also expensive.